Disinformation as a Tool for Recruitment by Terrorist Groups in Nigeria - Idris Mohammed; Eric Msughter Aondover; Omolara Oluwabusayo Akin-Odukoya; Ekpali Joseph Saint (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2025)
Terrorist organizations in Nigeria, such as Boko Haram and ISWAP (Islamic State West Africa Province), have increasingly utilized disinformation as a strategic tool to manipulate public opinion and recruit members. This study examines the mechanisms, channels, and effects of disinformation campaigns, analyzing their impact on radicalization and recruitment. Using a qualitative approach, this research explores case studies, social media propaganda, and counter-narratives to assess the effectiveness of terrorist recruitment through disinformation. The findings highlight the urgent need for counterstrategies that involve media literacy, governmental intervention, and community resilience programs. The paper argues that disinformation plays a significant role in the recruitment strategies of terrorist groups in Nigeria, such as Boko Haram and ISWAP (Islamic State West Africa Province). These groups use false narratives, propaganda, and social media manipulation to radicalize and recruit individuals, particularly in vulnerable communities. The paper concludes that disinformation is a critical tool used by terrorist groups in Nigeria to manipulate narratives, radicalize individuals, and recruit members. Boko Haram, ISWAP (Islamic State West Africa Province), and other extremist factions leverage fake news, conspiracy theories, and misinformation to exploit vulnerable populations.